Analisis Pengendalian Kualitas (Quality Control) Dalam Meningkatkan Produk Pupuk Organik (Komposter) Dan Daur Ulang Di Wilayah Sunter jaya - Ja, Yohanes Jogo; Heriyanto, Yayak (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study aims to analyze quality control in improving organic fertilizer (composters) and recycling products in the Sunter Jaya area. In this study, quantitative and primary data sources were used with questionnaires. The population in this study is all people involved in the production process. The analysis method used in this research is Statistical Quality Control (SQC). The results of the study show that in the production process of organic fertilizer (composters) and recycling in the Sunter Jaya area, the average product defect rate is 1%, with the highest defect rate being in ineffective solid products at 5%. In this study, other defects such as odor and contamination had a percentage of 0%, which means that the production results were in the good category.